2015
DOI: 10.1186/s13620-015-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three therapeutic alternatives for the early treatment of ovine pregnancy toxaemia

Abstract: BackgroundOvine pregnancy toxaemia is a common metabolic disorder of ewes due to increased foetal energy requirements in late pregnancy. This pathology is a metabolic condition characterized by hypoglycaemia and hyperketonaemia resulting in the inability of the animal to maintain an adequate energy balance. The response to treatment is effective, if it is started in the early stages of the disease, when irreversible neurological injuries have not yet been established. The aim was to evaluate three therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(48 reference statements)
1
15
0
1
Order By: Relevance
“…Cal‐Pereyra et al . () noted that glycaemia values were 2.71 ± 0.66, 2.95 ± 0.57 and 3.00 ± 0.57 mmol/L, respectively, in three groups of sheep carrying a singleton foetus at day 130 of gestation, while Sigurdsson () reported that the average glycaemia value was 2.88 ± 0.56 mmol/L in sheep carrying singletons or twins on day 130 of gestation.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Cal‐Pereyra et al . () noted that glycaemia values were 2.71 ± 0.66, 2.95 ± 0.57 and 3.00 ± 0.57 mmol/L, respectively, in three groups of sheep carrying a singleton foetus at day 130 of gestation, while Sigurdsson () reported that the average glycaemia value was 2.88 ± 0.56 mmol/L in sheep carrying singletons or twins on day 130 of gestation.…”
Section: Discussionsupporting
confidence: 85%
“…It was found by Cal-Pereyra et al (2015a) that glycaemia values in two groups of sheep carrying singletons on day 130 of gestation were 3.19 AE 0.45 and 3.04 AE 0.53 mmol/L, respectively. Cal-Pereyra et al (2015b) noted that glycaemia values were 2.71 AE 0.66, 2.95 AE 0.57 and 3.00 AE 0.57 mmol/L, respectively, in three groups of sheep carrying a singleton foetus at day 130 of gestation, while Sigurdsson (1988) reported that the average glycaemia value was 2.88 AE 0.56 mmol/L in sheep carrying singletons or twins on day 130 of gestation. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnancy toxemia is a metabolic disease caused by a negative energy balance that result in excessive lipid metabolism and ketosis (Araújo et al, 2018). Occurs generally in ewes carrying two or more foetuses and has a high mortality rate (Cal-Pereyra et al, 2015b). In obese ewes, the fat storage formed around the rumen predisposes the occurrence of the disease by reducing dry matter intake (Lacetera et al, 2001;Araújo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%